The Influence Of Expanded Marketing on Visiting Interest to Lawata Beach in Bima, Indonesia - Sri Ernawati Zunaidin (Journal of Business and Management Review, 2021)
The development paradigm in many countries is currently more oriented towards the service sector and industry, including the tourism industry. In the tourism system, the marketing strategy carried out on tourist objects is an important element in supporting the desire of tourists to visit. This study aims to determine and analyze whether expanded marketing affects the visiting decision Lawata Beach. This study uses a mix method quantitative and a qualitative. The population in this study are tourists who have visited lawata beach tourist destinations in Bima City. Sampling with purposive sampling technique, where the determination of the sample based on certain criteria that are tailored to the needs of the study. The sample in this study amounted to 100 people with the research instrument using a questionnaire with a Likert scale. Data analysis used simple linear regression, partial test with t test. To test the effect between variables using SPSS (Statistical Service Product Solutions) version 20.00 and SWOT analysis. The results of the study stated that expanded marketing had a positive and significant effect on the Visiting Decision Lawata Beach Bima City and from the results of the SWOT analysis, the Bima City government had to always develop attractive tourist attractions, making Lawata Beach an economic creative area and adding supporting facilities on the Lawata beach, facilities and infrastructure can add attractiveness and increase competitiveness with tourist objects in other areas.